Role of education in the integration of marginalized social groups into the labour market - Kulić, Marina (Economic Outlook, 2024)
The subject of the research paper is the analysis and examination of the role of education in the integration of marginalized groups into the labor market. The goal of the work leads to understanding the connection between the education of these specific social groups, the level of education and employment, and the possibilities and ways to synergize these social groups with the labor market. This research shows the possibilities and chances for education of individuals from marginalized social groups in the Republic of Serbia. The focus of the research was on how and to what extent acquired formal education can help individuals from marginalized groups to find an adequate job and thereby increase the quality of their life. The descriptive method, document analysis, questionnaire and analysis were used in the preparation of this research paper. The conclusion is that today, marginalized social groups, although they have the opportunity to later acquire formal primary and secondary education and have the support of institutions for this, are not sufficiently motivated in education and professional training. It is necessary to find more effective strategies and policies to motivate marginalized individuals and groups to become more involved in formal and informal forms of education.